B(3, 4, 5-F3H2C6)3 Lewis acid-catalysed C3-allylation of indoles. Issue 16 (17th April 2023) - Alotaibi, Nusaybah; Babaahmadi, Rasool; Pramanik, Milan; Kaehler, Tanja; Dasgupta, Ayan; Richards, Emma; Ariafard, Alireza; Wirth, Thomas; Melen, Rebecca L.
Abstract : Herein we report the B(3, 4, 5-F3 H2 C6 )3 -catalysed C3-allylation of indoles using allylic esters. Abstract : Herein we report the B(3, 4, 5-F3 H2 C6 )3 -catalysed C3-allylation of indoles using allylic esters. 25 examples of C3-allylated products are presented in up to 97% yield. The mechanism for the reaction was explored using detailed Density Functional Theory (DFT) studies.